(3MhGOK GdReGf hhajGJ GdTjhN hGdCbQGfs - (3CMeO Hf YeQ GdCfUGQj GdTgjQ HGHf GdMeUj GdTGaYjs; (3TgGH GdOjf CHh GdaVd CMeO Hf Ydj Hf MLQ GdYSbdGfi,J (B852 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdHGbi hGdHbGA ef UaGJ PGJg s
(3ai cTa GdXfhf (B1/693 (3MhGOK GdReGf hCHfGDg hhajGJ GdCYjGf hCHfGDgs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B173s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B118 s
Keywords: (3GdJGQjNs